Revisiting Polybia paulista wasp venom using shotgun proteomics - Insights into the N-linked glycosylated venom proteins - Souza, Caroline Lacerra de [UNESP]; Aparecido dos Santos-Pinto, Jose Roberto [UNESP]; Esteves, Franciele Grego [UNESP]; Perez-Riverol, Amilcar [UNESP]; Romani Fernandes, Luis Gustavo; Zollner, Ricardo de Lima; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2019)
The partial proteome of Polybia paulista wasp venom was previously reported elsewhere using a gel-dependent approach and resulted in the identification of a limited number of venom toxins. Here, we reinvestigated the P. paulista venom using a gel-free shotgun proteomic approach; the highly dynamic range of this approach facilitated the detection and identification of 1673 proteins, of which 23 venom proteins presented N-linked glycosylation as a posttranslational modification. Three different molecular forms of PLAT were identified as allergenic proteins, and two of these forms were modified by N-linked glycosylation. This study reveals an extensive repertoire of hitherto undescribed proteins that were classified into the following six different functional groups: (i) typical venom proteins; (ii) proteins related to the folding/conformation and PTMs of toxins; (iii) proteins that protect toxins from oxidative stress; (iv) proteins involved in chemical communication; (v) housekeeping proteins; and (vi) uncharacterized proteins. It was possible to identify venom toxin-like proteins that are commonly reported in other animal venoms, including arthropods such as spiders and scorpions. Thus, the findings reported here may contribute to improving our understanding of the composition of P. paulista venom, its envenoming mechanism and the pathologies experienced by the victim after the wasp stinging accident. Biological significance: The present study significantly expanded the number of proteins identified in P. paulista venom, contributing to improvements in our understanding of the envenoming mechanism produced by sting accidents caused by this wasp. For example, novel wasp venom neurotoxins have been identified, but no studies have assessed the presence of this type of toxin in social wasp venoms. In addition, 23 N-linked glycosylated venom proteins were identified in the P. paulista venom proteome, and some of these proteins might be relevant allergens that are immunoreactive to human IgE.
Keywords: Hymenoptera venom; Toxins; Neurotoxins; Allergy; Glycosylation; Mass spectrometry